Experimental analysis to improve charge/discharge of thermal energy storage in phase change materials using helical coil and porous metal foam. (25th November 2022) - Karimi, Ali Reza; Siavashi, Majid; Tahmasbi, Milad; Norouzi, Amir Mohammad
Abstract: The use of phase change materials (PCM) for latent heat thermal energy storage (LHTES) is a common method of storing thermal energy in buildings. Because the thermal conductivity of the PCMs is low, so the rate of their energy charge/discharge would be confined. To overcome this issue, a new design is proposed using helical coil to maximize the contact surface between the heat transfer fluid (HTF) and the PCM. Both sides of the helical coil are filled with PCM, while in the inner region, copper metal foams (porosity of 0.9 and density of 12 PPI) are utilized for heat transfer rate enhancement. Effects of various parameters, including the inlet HTF flow rate, its temperature, and use of porous media on thermal energy storage performance in charge and discharge processes are analyzed experimentally. Six thermocouples are placed inside the PCM in different regions and melting and solidification processes are recorded using a thermal imaging camera. Results are presented in terms of temperature variation in different regions, temperature contours, mean temperature response, Stefan number, the charge/discharge time, and the extracted power of discharge. The results reveal that using porous media can remarkably reduce the charge/discharge time up to 57 %, which is depended on the inlet working fluid temperature. The charging time reduction is higher when the inlet HTF temperature increases. When the flow rate of HTF is increased, the charging time can be slightly shortened, while this effect becomes dominant when using porous media. Use of porous media could also accelerate the discharge time, while a faster discharge rate was observed for lower HTF flow rates during discharging the stored energy. Also, a lower initial temperature of the inlet HTF provides faster depletion rate. Graphical abstract: Unlabelled Image Highlights: A new design of TES system with helical coil and porous foam is proposed. Helical coil and porous media could substantially improve the heat transfer. Effects of HTF temperature & rate on charge & discharge process are tested. Porous foams could reduce the charge/discharge time up to 57 %. Higher (lower) flow rates are recommended to reduce the charge (discharge) time.